La tunantada en el desarrollo musical en estudiantes de saxofón del Instituto Superior de Música Público Daniel Alomía Robles, 2023 - Sánchez Melgarejo, Alberto Gilber (2025)
The main objective of the thesis entitled “The tunantada in the musical development of saxophone students of the Instituto Superior de Música Público Daniel Alomía Robles 2023” was to analyze the musical elements, techniques and interpretative characteristics of the tunantada for its application in the musical training of saxophonists. A qualitative methodology with phenomenological design, descriptive level and basic research was used. The population consisted of all ISMPDAR students. The study sample included 5 saxophone students, 4 of whom belonged to the Music Education and Arts major, and 1 to the Music major (artist), who provided information through semi-structured interviews and participant observation. The results showed that the tunantada contributes to the technical and expressive development of saxophonists through the use of musical ornaments such as appoggiaturas, mordents, trills and vibratos. The main objective of the thesis entitled “The tunantada in the musical development of saxophone students of the Instituto Superior de Música Público Daniel Alomía Robles 2023” was to analyze the musical elements, techniques and interpretative characteristics of the tunantada for its application in the musical training of saxophonists. A qualitative methodology with phenomenological design, descriptive level and basic research was used. It is concluded that the tunantada strengthens the cultural identity and musical development of the students, encouraging advanced techniques of interpretation and expressiveness on the saxophone. It is recommended that this folk music be integrated into formal education for its preservation and enrichment.